Influence of micronutrients on the male sterility, on upland wheat and on rice and soybean yields, in red-yellow latosol - Silva, Ady Raul da; Andrade, José Maria Vilela de (Pesquisa Agropecuaria Brasileira, 2014)
In a virgin red-yellow latosol, typical of high plateaus, the influence of micronutrients on the wheat male sterility ("chochamento") and their residual effects on yields of wheat, rice and soybeans, was evaluated in three years. Boron was the micronutrient responsible for the control of wheat male sterility, as it has been previously observed, in lowland irrigated wheat. The residual effect of 0.65 kg/ha of boron in the borax was efficient in the second year and 1.3 kg/ha of boron in the FTE BR 12 was efficient also in the third year. The boron did not lower the yields of rice and soybeans except when applied in the row, at rate eight times higher than the recommended dosis. Zinc had no effect on the wheat yield but its residual effect increased the rice and soybean yield. The ratio cost/benefit 11.1 kg/ha of wheat to 1 of borax and 72.7 kg/ha of wheat to 1 of FTE BR 12 is now three times lower, because the boron is effective, at least, for three years.